Systematic review of literature to evaluate global distribution of species of the Sporothrix genus stored in culture collections - Morgado, Debora Salgado; Castro, Rodolfo; Ribeiro-Alves, Marcelo; Corrêa-Moreira, Danielly; Silva, Júlio Castro Alves de Lima e; Menezes, Rodrigo Caldas; Oliveira, Manoel Marques Evangelista (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Sporotrichosis is a subcutaneous mycosis caused by fungi of the genus Sporothrix sp. Phenotypic and genotypic differences have been associated with their geographic distribution, virulence, or clinical manifestation of sporotrichosis. In the past decade, the interest in identifying species of the Sporothrix sp. has been increasing, due to its epidemiological importance and, in consequence, is important to know how to preserve them for future studies, in culture collection. Aims The purposes of this study were to analyze the global distribution of environmental isolates and/or causal agents of sporotrichosis identified by polyphasic taxonomy, with mandatory use of molecular identification, and to evaluate the percentages and distribution of isolates stored in culture collections. Methods A systematic review of articles on animal and human sporotrichosis and/or environmental isolation of the fungus, from 2007 to 2023, was done. Results: Our results demonstrated that, S. globosa, S. schenckii, and S. brasiliensis were the most identified species. With respect to the deposit and maintenance of species, we observed that only 17% of the strains of Sporothrix sp. isolated in the world are preserved in a culture collection. Conclusions This systematic review confirmed a difficulty in obtaining the frequency of Sporothrix species stored in culture collection and insufficient data on the molecular identification mainly of animal sporotrichosis and isolation of Sporothrix sp. in environmental samples.